Effect of sensory exposure on liking for fat- or sugar-reduced biscuits. (1st December 2015) - Biguzzi, Coralie; Lange, Christine; Schlich, Pascal
Abstract: This study investigates the effect of exposure to fat- or sugar-reduced biscuits on liking for these products. Two sets of biscuits were manufactured, each including a standard variant and 4 variants differing by the level of reduction of either fat or sugar content, to 33% of fat content or 28% of sugar content. Biscuit consumers were recruited to eat either the fat (n = 113) or the sugar-reduced set of biscuits (n = 106). They participated in 5 testing sessions, once a week, in laboratory conditions. During each session, they rated their liking of the 5 variants. At the end of each of the 4 first sessions, consumers were given 16 biscuits for their home consumption during the week. Participants were split into 3 groups of exposure: every week, a control group received the standard variant, a "direct" group received the most reduced variant and a "stepwise" group received a more and more reduced variant. After both control and stepwise exposure, almost no evolution of liking was observed. At the end of the direct exposure period to the 33% fat-reduced variant, liking for this variant significantly improved. On the contrary, after the direct exposure to the 28% sugar-reduced variant, liking only improved for 9 and 16% sugar-reduced variants. Highlights: Liking for a 33% fat-reduced biscuit increased after 4 weeks of exposure. No impact of liking of a 4-week exposure to a 28% sugar-reduced biscuit. Exposure to a 28% sugar-reduced biscuit increase liking for less reduced variants. The biscuit industry should rather look for fat than sugar reduction. No evolution of liking after a stepwise exposure to fat- or sugar-reduced biscuits.